Montelukast as an alternative to low-dose inhaled corticosteroids in the management of mild asthma (the SIMPLE trial): An open-label effectiveness trial - McIvor, R Andrew (Pulsus Group Inc, 2009)
OBJECTIVE: To evaluate the effectiveness of montelukast as monotherapy for patients with mild asthma who remain uncontrolled or unsatisfied while on inhaled corticosteroid (ICS) monotherapy. DESIGN: A multicentre, open-label study. Patients (six years of age or older) had ICS therapy discontinued and were treated with orally administered montelukast once daily for six weeks. MAIN OUTCOME MEASURES: The primary outcome measure was the rate at which asthma symptom control was achieved or maintained after six weeks of treatment. The secondary outcome measures were to compare compliance and physician satisfaction, and to further assess the safety and tolerability of montelukast. RESULTS: Of the 534 patients enrolled, 481 (90.1%) completed the study. Mean (± SD) age was 27.8±19.0 years. The number of patients with uncontrolled symptoms decreased from 455 (85.2%) at baseline to 143 (26.8%) at week 6 (P<0.001), and mean Asthma Control Questionnaire score decreased from 1.4±0.8 to 0.6±0.6 (P<0.001), representing a clinically significant improvement. Of the 79 patients with controlled asthma symptoms at baseline, 73.4% maintained asthma control at week 6. Compliance to asthma therapy increased from 41% at baseline for ICS to 88% at week 6 for montelukast (P<0.001). Physician satisfaction with treatment increased from 43% to 85% (P<0.001) and patient satisfaction increased from 45% at baseline to 94% at week 6. No serious adverse events were reported over the course of the study. CONCLUSION: Montelukast is an effective and well-tolerated alternative to ICS treatment in patients with mild asthma who are uncontrolled or unsatisfied with low-dose ICS therapy.